Construction de Bruijn sequence based on whole LFSR with 4 cycles - Congwei ZHOU; Bin HU; Jie GUAN (Tongxin xuebao)
In order to improve the construction efficiency and widen the application depth of cycle-joining method, from the view of the number of cycles in the cycle structure, a method for constructing de Bruijn sequence based on whole LFSR with 4 cycles was proposed.Based on the characteristic of cascade connection of LFSR, the cycle structure of a class of cascaded feedback shift registers was determined.Accordingly, the exact number of whole n-order LFSR with 4 cycles was given, and the total number of n-order de Bruijn sequences constructed from whole n-order LFSR with 4 cycles as well.